An Experimental Investigation on Fatigue Properties of AA3003-H14 Aluminum alloy Friction Stir Welds (Journal of Engineering, 2011)
AA3003-H14 aluminum alloy plates were welded by friction stir welding and TIG welding.Fatigue properties of the welded joints were evaluated based on the superior tensile properties forFSW at 1500 rpm rotational speed and 80 mm/min welding speed. However, there is not muchinformation available on effect of welding parameters with evolution of fatigue life of friction stirwelds. The present study experimentally analyzed fatigue properties for base, FSW, and TIG weldsof AA 3003-H14 aluminum alloy. Fatigue properties of FSW joints were slightly lower than thebase metal and higher than TIG welding.